Direct measurement of the magnetic penetration depth by magnetic force microscopy - Kim, Jeehoon (2012)
We present an experimental approach using magnetic force microscopy for measurements of the absolute value of the magnetic penetration depth (lambda) in superconductors. Lambda is obtained in a simple and robust way without introducing any tip modeling procedure via direct comparison of the Meissner response curves for a material of interest to those measured on a reference sample. Using a well characterized Nb film as a reference, we determine the absolute value of lambda in a Ba(Fe0.92Co0.08)2As2 single crystal and a MgB2 thin film through a comparative experiment. Our apparatus features simultaneous loading of multiple samples, and allows straightforward measurement of the absolute value of lambda in superconducting thin film or single crystal samples.